PEMASANGAN ALAT PERAGA KAMPANYE TANPA SEIZIN PEMILIK TEMPAT - Hutapea, Brahmantya Putra; Simandjuntak, Jeremia Putra Ferliano; Sousa, Freidelino P.R.A. de (The Juris, 2024)
The Campaigns as a part of the stages of elections, are regulated by KPU Regulation Number 23 of 2018 concerning General Election Campaigns. However, the implementation of the campaign carried out by the campaign participants, was not in line with the provisions of campaigns, one of which was the installation of campaign props without the permission of the owner of the place. Campaign props that are part of the election should also be supervised by the KPU. If the installation of campaign props does not follow the provisions and then no action is taken by the KPU to issue a decision, then for this act of silence, the KPU is deemed to have issued a decision that is the same as a written State Administrative Decree containing a rejection which is referred to as a negative or fictitious negative decision. These violations can be resolved through Bawaslu as an institution that is given authority by-laws, one of which is to receive, examine, review, and decide on administrative election violations. Apart from that, when the process in Bawaslu still did not result solution, the process can be resolved by the PTUN.